Regional Planning Pathways to Forest Sustainability and Disaster Resilience in Northern Sumatra: English - Lubis, Arga Abdi Rafiud Darajat (CV. ARGA FARMA, 2026)
Late November 2025 marked an escalation in flood–landslide disasters across Northern Sumatra, associated with Tropical Cyclone Senyar and multi-day extreme rainfall over the Malacca Strait region (Badan Meteorologi, Klimatologi, dan Geofisika [BMKG], 2025). Disaster reporting in Aceh indicates that heavy rainfall was the proximate trigger, while upstream forest damage was suspected to have amplified impacts, consistent with compound climate–land-system hazards. Climate attribution evidence further suggests that anthropogenic warming increased the intensity of extreme rainfall spells affecting the Malacca Strait region, implying that planning baselines derived from historical climatology risk underestimating future hazard magnitudes. This study develops a planning-oriented pathway model linking land-system change (forest loss, riparian disruption, bare-soil expansion) to disaster outcomes (flood footprints, infrastructure breakpoints, displacement) and to carbon co-benefits (avoided emissions and restoration potential). The expected contribution is a replicable “planning-to-risk” workflow that prioritizes sub-watersheds where spatial planning compliance and nature-based solutions can jointly reduce debris-flood risk while strengthening forest-carbon retention.